The regulation of 2,3-butanediol synthesis in Klebsiella pneumoniae as revealed by gene over-expressions and metabolic flux analysis - Lu, Mingshou; Park, Changhun; Lee, Soojin; Kim, Borim; Oh, Min-Kyu; Um, Youngsoon; Kim, Jungwook; Lee, Jinwon (Springer Verlag, 2014)
A variety of microorganism species are able naturally to produce 2,3-butanediol (2,3-BDO), although only a few of them are suitable for consideration as having potential for mass production purposes. Klebsiella pneumoniae (K. pneumoniae) is one such strain which has been widely studied and used industrially to produce 2,3-BDO. In the central carbon metabolism of K. pneumoniae, the 2,3-BDO synthesis pathway is dominated by three essential enzymes, namely acetolactate decarboxylase, acetolactate synthase, and butanediol dehydrogenase, which are encoded by the budA, budB, and budC genes, respectively. The mechanisms of the three enzymes have been characterized with regard to their function and roles in 2,3-BDO synthesis and cell growth (Blomqvist et al. in J Bacteriol 175(5):1392-1404, 1993), while a few studies have focused on the cooperative mechanisms of the three enzymes and their mutual interactions. Therefore, the K. pneumoniae KCTC2242::Delta wabG wild-type strain was utilized to reconstruct seven new mutants by single, double, and triple overexpression of the three enzymes key to this study. Subsequently, continuous cultures were performed to obtain steady-state metabolism in the organisms and experimental data were analyzed by metabolic flux analysis (MFA) to determine the regulation mechanisms. The MFA results showed that the seven overexpressed mutants all exhibited enhanced 2,3-BDO production, and the strain overexpressing the budBA gene produced the highest yield. While the enzyme encoded by the budA gene produced branched-chain amino acids which were favorable for cell growth, the budB gene enzyme rapidly enhanced the conversion of acetolactate to acetoin in an oxygen-dependent manner, and the budC gene enzyme catalyzed the reversible conversion of acetoin to 2,3-BDO and regulated the intracellular NAD(+)/NADH balance.